Gated Quantum Structures in Two-Dimensional Semiconductors - Boddison-Chouinard, Justin (Université d'Ottawa / University of Ottawa, 2022)
The family of semiconducting 2H-phase group-VI transition metal dichalcogenides (TMDs) have been suggested to be promising candidates for hosting optically accessible spin qubits due to their desirable optical and electrical properties, however, experimental progress towards this goal has been impeded by the difficulties associated with the fabrication of clean structures with quality contacts. In this thesis, we present the complex process for obtaining functional contacts to two particular TMDs, molybdenum disulfide (MoS2) and tungsten diselenide (WSe2), from which we use as the foundation for the fabrication of three important gate defined quantum structures: quantum dots, a charge detector, and a long 1D channel. These structures all play an important role in furthering the understanding of these materials and are the building blocks for achieving functional spin qubits. More precisely, we investigate the contact resistances associated with various cleaning procedures and contact architectures and report a recipe that results in an ultra-low contact resistance even at cryogenic temperatures. We then demonstrate electrical control of hole quantum dots, the host of the spin qubit, in gated heterostructure devices based on monolayer WSe2 and study its properties. With a similar structure, we demonstrate that a gate-defined nano-constriction is sensitive to the charge occupation of a nearby quantum dot and is therefore suitable to be used as a charge sensor, a valuable component of elaborate quantum circuits. Finally, we demonstrate the realization of a gate-defined quantum confined 1D channel in a high mobility monolayer WSe2 sample and observe an anomalous conductance quantization in units of e2/h. These results pave the way for the development of quantum devices based on electrostatically confined quantum dots defined in semiconducting TMDs and push forward our understanding of their electronic properties.
Keywords: 2D Materials; Gated Quantum Structures; Quantum Dots; van der Waals Heterostructures